Women's Entrepreneurial Ecosystem in Nepal: A Study Based on Kathmandu Valley - Upasna Acharya; Chittaranjan Pandey (Westcliff University, 2018)
Entrepreneurship, traditionally seen as a male preserve, has witnessed increasing participation from females in recent years. Across the world, the number of enterprises being run by women is growing exponentially. Nepal is not an exception to this emerging trend. However, there are embedded structural and socio-cultural constraints which pose a challenge to the growth of women entrepreneurs and the stability of the entrepreneurial ecosystem in Nepal. Through qualitative research, this article attempts to study the phenomenon of the entrepreneurship of women and explore the status-quo and the policy framework for female entrepreneurs in Nepal. This article explores the current entrepreneurial environment for Nepalese women, as well as the issues and challenges associated with it. This study was conducted within the Kathmandu valley and samples of the study were drawn from various stakeholders comprising of financial institutions, government agencies, I/NGOs, venture capitalists and women entrepreneurs. The data required for the study was obtained via in-depth personal interviews, key informants' interviews and literature reviews from a variety of well-researched journals and articles. The six- factor model, inclusive of social, economic, competitive, facilitating, locational and political aspects identified by Bulsara, Chandwani and Gandhi (2014), has been assessed to understand the inherent challenges. Additionally, a political, economic, social, technological, environmental and legal (PESTEL) framework has been used to analyse insights from current women in the Nepalese entrepreneurial ecosystem. This study revealed that the process of lengthy documentation, bureaucratic hassles, political uncertainty, unconducive business environments, corruption, strikes, and unionization are the concurrent factors affecting the entrepreneurial environment in Nepal. On the policy side, though an amendment has been made in the Nepal Enterprise Act to support the entrepreneurship of women, the effectiveness of the policy support is still questioned.